Underpotential deposition: From planar surfaces to nanoparticles - Oviedo, Oscar Alejandro (2014)
An overview is given of selected theoretical, experimental and computer simulation research on thermodynamic modeling applied to the metal underpotential deposition. Focus is made mainly on the last 20 years. The upd-theory on planar surfaces is revisited and the thermodynamic framework is extended to consider underpotential deposition on nanoparticles and to include anion coadsorption, solvation and double layer charging. Results from molecular dynamics and Monte Carlo simulations are shown for systems of experimental interest. At the end some perspectives for further advanced modeling of the present problem are given